Combination of rapamycin and adipose-derived mesenchymal stromal cells enhances therapeutic potential for osteoarthritis - Damien Veret; Gautier Tejedor; Esther Perez; Alison Chomette; Maylis Farno; Rosanna Ferreira-Lopez; Louis Dagneaux; Yves-Marie Pers; Christian Jorgsensen; Claire Gondeau; Jean-Marc Brondello (Stem Cell Research & Therapy, 2025)
Abstract Background The regenerative potential of mesenchymal stromal/stem cells (MSCs) has been extensively studied in clinical trials in the past decade. However, despite the promising regenerative properties documented in preclinical studies, for instance in osteoarthritis (OA), the therapeutic translation of these results in patients has not been fully conclusive. One factor contributing to this therapeutic barrier could be the presence of senescent cells in OA joints. Methods This study evaluated a novel approach to OA treatment by combining adipose tissue-derived MSCs (AD-MSCs) with rapamycin, a clinically approved immunosuppressive drug with anti-senescence properties. First, rapamycin effects on senescence and fibrosis markers were investigated in freshly isolated OA chondrocytes by immunostaining. Next, the in vitro differentiation capacities of AD-MSCs, their regulatory immune functions on activated immune cells and their regenerative effects on OA chondrocyte signature were assessed in the presence of rapamycin. Results In OA chondrocytes, rapamycin reduced the senescence marker p15INK4B and the fibrosis marker COL1A1 without affecting the expression of the master chondrogenic markers SOX9 and COL2. Rapamycin also enhanced AD-MSC differentiation into chondrocytes and reduced their differentiation into adipocytes. In addition, rapamycin improved AD-MSC immunoregulatory functions by promoting the expression of immunosuppressive factors, such as IDO1, PTGS2 and also CD274 (encoding PD-L1). Finally, RNA sequencing analysis showed that in the presence of rapamycin, AD-MSCs displayed improved chondroprotective regenerative effects on co-cultured OA chondrocytes. Conclusions Our findings suggest that the rapamycin and AD-MSC combination enhances the therapeutic efficacy of these cells in senescence-driven degenerative diseases such as OA, notably by improving their anti-fibrotic and anti-inflammatory properties. Graphical abstract